2017
DOI: 10.1002/jso.24503
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of mitotic rate in cutaneous melanoma: A study using the national cancer data base

Abstract: MR reporting increased dramatically after the introduction of AJCC7; however, disparities in reporting remain across facility types. Further investigation of procedures performed in academic settings that may influence reporting of MR is warranted. J. Surg. Oncol. 2017;115:281-286. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Primary melanoma (M) mitotic rate (MR) is considered to be an important adverse predictor for overall survival: as the number of mitoses/mm 2 increases, survival decreases . In multivariate analyses, MR was found to be the second powerful predictor of survival outcome, after Breslow's thickness, in patients with localized M .…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Primary melanoma (M) mitotic rate (MR) is considered to be an important adverse predictor for overall survival: as the number of mitoses/mm 2 increases, survival decreases . In multivariate analyses, MR was found to be the second powerful predictor of survival outcome, after Breslow's thickness, in patients with localized M .…”
mentioning
confidence: 99%
“…The 2009 Committee, in fact, concluded that the histologic diagnosis of all primary Ms should include a MR determination, using a standardized approach, the so‐called “hot spot” method . In this regard, Lorimer et al have examined 107 194 patients affected by M from 2010 to 2013; MR was reported in only 80 039 cases (74.7%). According to the Authors, for the remaining 27 155 patients, the lack of MR reporting can have important implications for proper staging and prognostication, arguing that with detailed pathological reports, clinicians may formulate more personalized and effective treatment plans .…”
mentioning
confidence: 99%
See 3 more Smart Citations